Evaluate the IL-33 and SOD In T2DM Iraqi Patients and Its Roles in Disease Development - AL-tameemi, Hamid; Ahmed Khalaf, Shahrazad; Abdulrazaq, Dina (JOURNAL OF MEDICAL AND HEALTH SCIENCE, 2024)
Background: Diabetes mellitus is a systematic disease associated with increase blood sugar which may occur due to defect with insulin synthesis or their action or both. The current study aimed to evaluate level of IL-33 in T2DM patients. Materials and methods: Fifty adult patients diagnosed previously with Type 2 diabetic mellitus, and 40 persons were selected as healthy control group. Age, random blood sugar, and Weight data were collected from all participates, and by using enzyme linked immune sorbent assay two biomarkers were analyze for assessment human IL-33, and SOD concentrations in the serum of both groups. Results: The result shown that there was non-significant difference in age and weight of patient group by compare with control. The result of RBS, shown there is highly significant increase in diabetic patient group in comparison with control group. The result parameter IL-33 shown there was significant increase in diabetic patient group in comparison with control group. Finally, there is significant decrease for SOD level in diabetic patient group in comparison with control group. Conclusion: The elevation of IL-33 may play a role in T2DM development and could potentially lead to novel therapeutic approaches development.